IC 8638 Extracting Minerals From Geothermal Brines: A Literature Study - Rolland L. Blake (The National Institute for Occupational Safety and Health (NIOSH), 1974)
The Bureau of Mines is concerned with extracting minerals from residual geothermal brines after their heat content and some demineralized water have been recovered. This literature study is based on a survey of the literature and discussions with individuals knowledgeable on various aspects of the subject. This report examines the potential of the domestic geothermal mineral resources, considers the technical problems involved, and outlines possible effects on the environment from reservoir fluid withdrawal and reinjection. Geothermal resources in the Western United States were extensively explored during the 1960's. Limited development operations included exploratory drilling and operating wells producing hot brine, separating steam for experimental electric power generation, and recovering minerals in solar evaporation ponds or in extraction plants. Interest in the recovery of minerals and salts from geothermal fluids waned because of corrosion and scaling problems and low or no market value of the mineral products. Most of these problems can be controlled with existing technology and careful planning of processes and equipment. Extracting geothermal minerals is technically feasible, but the problems of low or no market value for major mineral products, and insufficient amounts of more valuably major products, make mineral recovery uneconomical at present.